PENGARUH CURRENT RATIO DAN DEBT TO EQUITY RATIO TERHADAP FINANCIAL DISTRESS PADA SUBSEKTOR APPAREL AND LUXURY GOODS YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE TAHUN 2019-2023 - Dela Puspitasari; Ratna Dumilah (Program Studi Akuntansi, Fakultas Ilmu Sosial dan Humaniora, Universitas Ibrahimy Situbondo, 2026)
This study aims to investigate the influence of Current Ratio (CR) and Debt to Equity Ratio (DER) on financial distress. Utilizing a quantitative, descriptive associative method, the research collected 30 sample data from 6 purposively selected companies within the Apparel and Luxury Goods subsector listed on the Indonesia Stock Exchange (IDX) for the 2019-2023 period, drawn from a total population of 22 companies. Hypothesis testing was performed using panel data regression analysis with E-Views 12 software and a 5% confidence level. The findings indicate that CR and DER collectively influence financial distress (F-calculated 47.777715 > F-table 3.35, significance 0.000000 < 0.05), with an Adjusted R-squared of 91.68%, while the remaining 8.32% is influenced by other unexamined variables. Partially, CR shows a positive and significant influence (t-calculated 2.382174 > t-table, significance 0.0263 < 0.05), whereas DER exhibits a negative but not significant influence (t-calculated 0.891224 < t-table 2.051, significance 0.3825 > 0.05) on financial distress.